THE ROLE OF INFLAMMATORY REACTIONS AND HEMORHEOLOGICAL INDICATIONS IN PATIENTS WITH RESTENOSIS AFTER CORONARY ANGIOPLASTY, OPTIMIZATION OF TREATMENT - N. A. Panahova (Евразийский Кардиологический Журнал)
Purpose. The aim of the trial was to study the importance of immuno-inflammatory processes and hemo-rheological changes in patients suffering from stable coronary heart disease after coronary angioplasty and stenting, as well as establishing the clinical effect of treatment optimized with anti-inflammatory drugs and immune-correctors.Material and methods. The study included 103 patients in total and 64 patients with an implanted stent. Within 2-28 months after stent implantation, an angiographic study was performed with the definition of a coagulogram, C-reactive protein (CRP), fibrinogen, and pro-inflammatory cytokines - tumor necrosis factor (FNA-α), interleukins (IL), IL-6, IL-8 in the serum of patients with coronary artery disease.Results. After coronary angioplasty and stenting in patients with coronary artery disease, the average concentrations of CRP and cytokines were significantly higher compared with both the control group and the group without restenosis. This indicator in the groups with and without restenosis was 16.4±1.2 (intragroup variation 6-36) mg/L and 6.8±0.4 (intragroup variation 5-10) mg/L, respectively; p<0.001. And from cytokines, the concentration of IL-6 in groups with and without restenosis was respectively 3.5+0.2 and 18.7+3.1 (p<0.01). In the correlative analysis in the group with restenosis, the expected close relationship between TNF-alpha and IL-6 is equal to r = 0.707, p<0.01, between CRB and IL-6, equal to r = 0.575, p<0.01, and between TNF-alpha and IL-8, equal to r = 0.610, p<0.05.